2018
DOI: 10.3389/fonc.2018.00583
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of MUTYH Variants to Male Breast Cancer Risk: Results From a Multicenter Study in Italy

Abstract: Inherited mutations in BRCA1, and, mainly, BRCA2 genes are associated with increased risk of male breast cancer (MBC). Mutations in PALB2 and CHEK2 genes may also increase MBC risk. Overall, these genes are functionally linked to DNA repair pathways, highlighting the central role of genome maintenance in MBC genetic predisposition. MUTYH is a DNA repair gene whose biallelic germline variants cause MUTYH-associated polyposis (MAP) syndrome. Monoallelic MUTYH variants have been reported in families with both col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
(56 reference statements)
1
21
1
1
Order By: Relevance
“…The MBC patient with biallelic MUTYH pathogenic variants had phenotypic manifestations of MUTYH ‐associated adenomatous polyposis (MAP), whereas none of the two MBC patients with APC c.3920T>A variant had phenotypic features associated with familial adenomatous polyposis (FAP) or had first‐degree FH of FAP (Table ). Monoallelic MUTYH pathogenic variants were also detected and reported in another study …”
Section: Resultssupporting
confidence: 64%
“…The MBC patient with biallelic MUTYH pathogenic variants had phenotypic manifestations of MUTYH ‐associated adenomatous polyposis (MAP), whereas none of the two MBC patients with APC c.3920T>A variant had phenotypic features associated with familial adenomatous polyposis (FAP) or had first‐degree FH of FAP (Table ). Monoallelic MUTYH pathogenic variants were also detected and reported in another study …”
Section: Resultssupporting
confidence: 64%
“…Six heterozygous MUTYH mutations, including p.Tyr179Cys, p.Gly396Asp and p.Pro405Leu (c.1214C > T, P405L), resulted in an association in families with both BC and CRC, but not polyposis[ 84 ] even if two years later an extensive case-control study did not confirm the association between MUTYH variants and BC, but did not exclude BC susceptibility[ 89 ]. An interesting result is the finding of one male with biallelic germline MUTYH pathogenic variants in a large cohort of males with BC[ 90 ]. In the same study, no biallelic MUTYH mutations been reported in women from large BC cohorts.…”
Section: Role Of Mutyh In Other Cancersmentioning
confidence: 99%
“…U heterozygotů patogenní mutace MUTYH genu je popsáno asi 2krát zvý šené riziko rozvoje kolorektálního karci nomu (colorectal cancer -CRC) od 45 let (OR 1,5-2,1), které odpovídá riziku CRC u prvostupňových příbuzných pa cienta se sporadickým časným CRC [41]. Ně kte ré studie uvádějí také 2krát zvýšené riziko karcinomu prsu, především ve specifických populacích (židovská, holandská) [42], v italské populaci do konce i u mužů [43]. Mírně zvýšená nad běžné populační riziko jsou i rizika roz voje dalších nádorových onemocnění (dělohy, žaludku, jater), sumárně jsou však tato rizika stále spíše nízká, bez spe ciálních doporučení stran preventivního sledování [44].…”
Section: Atmunclassified